Theoretical Study of One-Intermediate Band Quantum Dot Solar Cell - Abou El-Maaty Aly; Ashraf Nasr (International Journal of Photoenergy)
The intermediate bands (IBs) between the valence and conduction bands play an important role in solar cells. Because the smaller energy photons than the bandgap energy can be used to promote charge carriers transfer to the conduction band and thereby the total output current increases while maintaining a large open circuit voltage. In this paper, the influence of the new band on the power conversion efficiency for the structure of the quantum dots intermediate band solar cell (QDIBSC) is theoretically investigated and studied. The time-independent Schrödinger equation is used to determine the optimum width and location of the intermediate band. Accordingly, achievement of maximum efficiency by changing the width of quantum dots and barrier distances is studied. Theoretical determination of the power conversion efficiency under the two different ranges of QD width is presented. From the obtained results, the maximum power conversion efficiency is about 70.42% for simple cubic quantum dot crystal under full concentration light. It is strongly dependent on the width of quantum dots and barrier distances.